Os caminhos da superação : o sucesso de jovens de classes populares no ensino superior - Pacheco, Carolina Corrêa (2021)
Higher education in Brazil has been developed belatedly, having since its implementation an overrepresentation of middle and upper classes; however, one of most significant changes in recent dec ades has been the increase in the entry of young people from t he popular classes to graduation. At the same time diverse studies show that the entry is just a barrier that even though being surpassed does not guarantee the permanence of these students that come from a popular origin. That being said, the present stud y sought to investigate the success cases of students of popular origins in higher education who have managed to graduate in highly demanded courses in prestigious education institutions. A nume rous amount of studies has already been developed about the ca uses and motives of evasion of these young people in higher education; but only a few have sought to analyse the success cases that could provide fundamental information to create measures seeki ng to face this matter. In theoretical terms an analysis of edu cational inequalities has been attempted that have been worked through reference authors such as Bernard Lahire, Pierre Bourdieu, Alain Coulon, James Coleman and Raymond Boudon among others. Th is qualitative research has been developed through semi struct ured interviews during the period of July 2020 to April 2021. The analyses of the obtained information has showed that the success from the students have come from a variety of factors since pub lic policies which provided the opportunity to access universi ties until the affiliation process that together with the construction of a ne w habitu s based on their backgroun d has enabled the permanence of the students in higher education corroborating th e reference authors